Practical contribution of women development army on growth monitoring and promotion service at Dembya and Gondar Zuria districts, Central Gondar Zone, North West Ethiopia: a community based mixed study - Esmael Ali Muhammad; Melkamu Tamir Hunegnaw; Kedir Abdela Gonete; Netsanet Worku; Kasahun Alemu; Zegeye Abebe; Tigist Astale; Getnet Mitike; Aysheshim Kassahun Belew (BMC, 2023)
Abstract Background The United Nations' Sustainable Development Goal (SDG)-2 aims to eliminate child hunger or end all forms of child malnutrition by 2030. To achieve this goal the cost-effective method is the implementation of growth monitoring and promotion service with the contribution of Women Development Army (WDA) as community volunteers. However, According to the data, the program's implementation varies throughout the country and lack of evidence on the practical contribution of the WDA to enhancing child nutritional care outcomes. Therefore this study aimed to determine practical contribution of WDA and associated factors on growth monitoring and promotion service in two rural districts of central Gondar zone, Northwest Ethiopia. Methods A community based mixed study was conducted from March 6 to April 7, 2022 among 615 Women Development Army. Multistage sampling technique was used to select study participants. A structured questionnaire was used to collect quantitative data and in-depth interview were used to generate qualitative information. Qualitative data were coded and grouped and discussed using identified themes. Binary logistic regression was fitted, odds ratio with 95% confidence interval was estimated to identify factors of practical contribution of WDA and qualitative data was analyzed using thematic analysis. Results In this study practical contribution of WDA on growth monitoring was 31.4% (95% CI: 28.0-35.3%). Having GMP training (AOR = 4.2, 95%CI: 1.63, 10.58), regular community conversation (AOR = 6.0, 95%CI: 3.12, 11.54), good knowledge about GMP (AOR = 2.1, 95%CI: 1.17, 3.83) and not having regular schedule of GMP service in the area (AOR = 0.04, 95%CI: 0.02, 0.09), were statistically significantly associated with practical contribution of growth monitoring. During in-depth interview, lack of training, low motivation or commitment among WDA and low communication between WDA and health extension workers were mentioned among the problems faced during growth monitoring service. Conclusion In this study, practical contribution of growth monitoring among WDA was low. GMP training regular community conversation, knowledge about GMP and regular schedule of GMP service in the local area were significantly associated for practical contribution of growth monitoring service. Lack of training, low motivation or commitment among WDA and low communication between WDA and health extension workers were reasons for did not contribute effectively for GMP service. Therefore, giving training for WDA and improving community conversation at kebeles level are important to improve GM service. .